Degradation of Riparian Tree Diversity on Spring Fed Drains and Its Impacts to Water Quality, East Java - Semiun, Chatarina Gradict; Arisoesilaningsih, Endang; Retnaningdyah, Catur (Journal of Tropical Life Science, 2013)
This research aimed to determine the impact of degradation riparian tree diversity on water quality along some spring to its drains in East Java. This descriptive research conducted in selected springs and itsdrains in Jember, Kediri, Pasuruan, and Malang on April 2012 to January 2013. We used a spring water of Meru Betiri National Park as a reference site. Quality of riparian trees diversity and water were sampled with three replication.Data were tabulated by statistical analyzed using cluster and Spearman correlation. The result showed that species richness ofriparian tree in spring water and its drains has found were 69 species belonging to 28 families. Moraceae was key family of natural riparian tree and almost all the spring and its drains (92.75 %) were grown by native trees except in Kediri. All observed spring were degrading comparing to the natural one in Meru Betiri National Park where trees grown in strata A to E, and shown a highest diversity index (H=3.2). All water spring were observed in high quality but water in its downstream become turbid depend on the quality of treesriparian diversity grown around spring waters. Quality of riparian diversity was strongly influenced by land use and human activities such as illegal logging, intensive agriculture, and settlement. There was a positive correlation between riparian tree diversity, water transparency and color, but it had a negative correlation with pH value of water.Low pH, high water transparency and colorless water were found in stations where we found high tree species richness, diversity index, riparian width and stratified of tree.Keywords: Diversity quality, riparian tree, spring water , water quality.